Comprehensive evaluation of wild Cordyceps cicadae from different geographical origins by TOPSIS method based on the macroscopic infrared spectroscopy (IR) fingerprint - Sun, Yan-fang; Kmonickova, Eva; Han, Rui-lian; Zhou, Wei; Yang, Kai-bao; Lu, Hong-fei; Wang, Zhang-qi; Zhao, Hongxin; Wang, Huigang (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2019)
Cordyceps cicadae is an entomogenous fungus that has been used as a valuable traditional Chinese herbal tonic, however, it can be difficult to discern the false from the genuine. In this study, the macroscopic IR fingerprint methods containing Fourier transform infrared spectroscopy (FT-IR) and second derivative infrared spectroscopy (SD-IR) were used to elucidate wild C. cicadae. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method was used to comprehensively evaluate C. cicadae from different geographical origins based on the macroscopic infrared spectroscopy (IR) fingerprint. The FT-IR spectra of C. cicadae exhibited the major characteristics of the absorptive peaks of carbohydrates, lipids and nucleosides at the position of 3291, 2925, 2845, 1651, 1547, 1455, 1080 and 950 cm−1. The high resolution of SD-IR further amplified the difference and revealed the potentially characteristic IR absorption spectrum. TOPSIS evaluation showed that C. cicadae from Anhui possess the strongest intensity of absorption bands among all the samples. Notably, FT-IR combined with SD-IR can effectively reveal the overall chemical components without damaging medicinal materials, and TOPSIS methods can provide a novel scientific evidence for comprehensively assessing different origins of wild C. cicadae. [Display omitted] •Chemical profiling of wild Cordyceps cicadae was firstly revealed by FT-IR combined with 2D-IR spectroscopy.•TOPSIS method comprehensively evaluates Cordyceps cicadae based on IR fingerprint.•Results provided a novel scientific evidence for comprehensively assessing wild Cordyceps cicadae.